2014
DOI: 10.1016/j.solmat.2014.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Removing the effect of striations in n-type silicon solar cells

Abstract: a b s t r a c tSeveral industrial n-type Czochralski silicon ingots were analysed on wafer and cell levels with ECN's bifacial n-type solar cell process. In some of the ingots, the solar cell performance in the very top drop of about 1% absolute with respect to cell from the middle part of the ingot. These cells show typical ring shaped pattern. After receiving a post-process anneal treatment at 200 1C, the efficiency nearly completly recover. We demonstrated that the improvement is due to bulk lifetime enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…N-type silicon has been long lauded for its low susceptibility to light-induced degradation such as boron-oxygen related degradation and the impact from metallic contaminants [19]. Although this material does indeed suffer from degradation induced by grown-in defects, which have been extensively studied [20], an investigation of LeTID on n-type silicon concluded that the defect either does not manifest itself or is not recombination active in ntype [17]. On the other hand, a study by Renevier et al demonstrated a carrier-induced instability in the lifetime of boron-diffused n-type wafers fired in the presence of a hydrogenrich dielectric when subject to either illuminated annealing or dark annealing [21].…”
Section: Introductionmentioning
confidence: 99%
“…N-type silicon has been long lauded for its low susceptibility to light-induced degradation such as boron-oxygen related degradation and the impact from metallic contaminants [19]. Although this material does indeed suffer from degradation induced by grown-in defects, which have been extensively studied [20], an investigation of LeTID on n-type silicon concluded that the defect either does not manifest itself or is not recombination active in ntype [17]. On the other hand, a study by Renevier et al demonstrated a carrier-induced instability in the lifetime of boron-diffused n-type wafers fired in the presence of a hydrogenrich dielectric when subject to either illuminated annealing or dark annealing [21].…”
Section: Introductionmentioning
confidence: 99%
“…In conventional, horizontal cut wafers, these are the causes of ring-like structures reported in other studies. [25,26] A square-like artifact in the middle of A2 of B2 is likely to be attributed to higher surface recombination from organic deposits from a paper division sheet during transport. As shown in the figures in Section 3.4, this feature disappeared after treatment with Piranha solution prior to heat treatment.…”
Section: Oxygen Measurementsmentioning
confidence: 99%
“…The advantages of the proposed method are now demonstrated using a diffused n-type Cz silicon wafer with a resistivity of 2.4 Ω cm and a The wafer is partially affected by striations (ring defect), 34,35 resulting in a spatially non-uniform lifetime distribution.…”
Section: Application To a Diffused Samplementioning
confidence: 99%